Analisis Islamic Service Quality Dalam Peningkatan Loyalitas Nasabah Bank Syariah - Yuliana Banung Agarini; Dwi Meilindri; Hilma Fanniar Rohman (Pascasarjana UIN Raden Mas Said Surakarta, 2026)
This study aims to analyze the influence of Islamic Service Quality (ISQ) on customer loyalty in Islamic banks, particularly in the Special Region of Yogyakarta (DIY), Indonesia. The ISQ concept emphasizes the application of Sharia values such as honesty, fairness, sincerity, professionalism, and trust in every aspect of service delivery. Customer loyalty serves as a crucial long-term success indicator for Islamic banks, reflecting the emotional attachment and commitment of customers to continue using the offered products and services. This study employs a qualitative approach using library research methods by reviewing relevant literature, scientific journals, and official documents. The findings indicate that ISQ has a significant impact on customer loyalty, with trust and professionalism identified as the most dominant dimensions. Strategies to strengthen customer loyalty include improving Sharia-based service quality, providing continuous employee training, innovating products, and implementing promotional strategies aligned with Islamic values. This study recommends that Islamic banks consistently reinforce the application of Sharia principles in their services to maintain customer trust and loyalty, especially in regions with high religious awareness such as Yogyakarta.